Common Fixed Point and Coupled Coincidence Point Theorems for Geraghty’s Type Contraction Mapping with Two Metrics Endowed with a Directed Graph - P. Charoensawan; W. Atiponrat (Journal of Mathematics)
The purpose of this paper is to present some existence and uniqueness results for common fixed point theorems for θ-ϕ contraction mappings with two metrics endowed with a directed graph. In addition, by using our main results, we obtain some results about coupled coincidence points endowed with a directed graph. Our results generalize those presented in previous papers.